Microclimatic characterization of tourist caves in Parque Nacional Cavernas do Peruaçu, Minas Gerais, Brazil - Gomes, Mauro; Santos, Darcy José dos; Azevedo, Úrsula Ruchkys de; Travassos, Luiz Eduardo Panisset (Sociedade & Natureza, 2021)
The cave environment has very peculiar atmospheric conditions thatdirectly influence the existence and maintenance of the set of biotic andabiotic, socioeconomic, and historical-cultural elements represented bythe caves or associated with them. In caves where tourist activities arecarried out, human presence can affect the delicate balance of theseconditions. This research was developed to characterize the cavemicroclimate of seven caves that make up the tourist circuit of theParque Nacional Cavernas do Peruaçu, located in the northern regionof the State of Minas Gerais, in the southeastern region of Brazil.Temperature and relative humidity data were collected by 41 automated meters that accumulated just over 110,300 records each.The research stands out for being one of the only long-term (2017 to2019) developed in the country. The analysis of this informationallowed not only to characterize the microclimate of the caves, but alsoto observe the relationship of these attributes with the internalmorphology and with the position that the caves are in relation to theregion's karst relief. The methodology developed by this research cansubsidize the Environmental Conditions Monitoring Program of theCaves to be implemented by the management of the National Park andthe identification of more sensitive environments inside the caves willallow the reorganization of the visitation to these attractions.